2011
DOI: 10.1007/s12134-011-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Minorities in the Mass Media: How Migrants Perceive Their Representation in Swiss Public Television

Abstract: Communication research highlights deficiencies in the media's representation of migrants. The study at hand analyzes these deficiencies from the perspective of the migrants concerned: How do they perceive their representation in the media, especially on television? And how do they assess the perceived situation with regard to immigrant integration? This topic has been examined in a qualitative pilot study based on six group discussions amongst migrants and Swiss citizens with an immigration background in the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Bell, Horn, and Roxas 2007;Boyle and Charles 2011;Hamer 2013;Llurda and Lasagabaster 2010). The study also revealed that the participants' perceptions were closely associated with the mass media as well as their life and Journal of Education for Teaching 151 teaching practicum experiences (Ripoll and Arcacia 2008;Santoro 2009;Trebbe and Schoenhagen 2011). It must be noted that this inquiry only explored the pre-service teachers' perceptions of immigrant children but not their actual engagement with them.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Bell, Horn, and Roxas 2007;Boyle and Charles 2011;Hamer 2013;Llurda and Lasagabaster 2010). The study also revealed that the participants' perceptions were closely associated with the mass media as well as their life and Journal of Education for Teaching 151 teaching practicum experiences (Ripoll and Arcacia 2008;Santoro 2009;Trebbe and Schoenhagen 2011). It must be noted that this inquiry only explored the pre-service teachers' perceptions of immigrant children but not their actual engagement with them.…”
Section: Resultsmentioning
confidence: 92%
“…In the focus group discussions, 11 participants admitted that the mass media coverage on newly arrived children from Mainland China heavily influenced how they saw these children (Ripoll and Arcacia 2008;Trebbe and Schoenhagen 2011). Unlike the other participants who had early life experiences with these children, these participants did not have any direct experience working with these immigrants before their practicum.…”
Section: Mass Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…The participants additionally also frequently mentioned that minorities, who also comprise social life, should be positively referred to in coursebooks. When similar researches regarding the representation of minorities are looked at, a research conducted by Trebbe and Schoenhagen (2011) was seen to search for an answer to the question of how minorities in Switzerland perceived their presence on television. The research eventually found that minorities of African or Turkish origin were represented badly on television.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic minorities are less likely to be portrayed in professional roles than ethnic majority members and are more likely to be portrayed as law enforcement officers or in blue collar jobs. Although some studies have suggested more diversification in the type of occupational roles for ethnic minority characters (Stroman, Merritt, & Matabane, 1989), the overall consensus remains that generally they are seldom represented in upper-class settings (Gray, 1989;Trebbe & Schoenhagen, 2011). Finally, the few studies focusing on occupational prestige have found that ethnic minorities are represented in less prestigious occupations (Eschholz et al, 2002;Signorielli, 2004Signorielli, , 2009.…”
Section: Women and Ethnic Minorities In Occupational Roles On Televisionmentioning
confidence: 99%